Stakeholder Collaboration Model in Implementing the Policy of Banning Fishing Gear Cantrang in Lamongan Regency - Siswantoro, Tri Yudi; Handoko, Rudy; Kusbandrijo, Bambang (Konsultan Surya Buanan, 2025)
This paper examines the stakeholder collaboration model in the implementation of the policy banning the use of Cantrang fishing gear in Lamongan Regency, Indonesia. The study highlights the importance of multi-stakeholder engagement in addressing the challenges posed by Cantrang fishing gear, which has been linked to overfishing and environmental degradation. The issue of Cantrang fishing gear, also known as seine net fishing, has become a contentious topic in Indonesia, particularly in coastal areas like Lamongan Regency. The use of this gear has been associated with significant ecological consequences, including the depletion of fish stocks and the destruction of marine habitats. For instance, studies have shown that Cantrang nets can indiscriminately capture not only target fish species but also juvenile fish and non-target species, leading to a decline in biodiversity. This indiscriminate catch poses a threat not only to the fish populations but also to the livelihoods of local fishermen who depend on sustainable fishing practices. Through qualitative analysis and case studies, the research identifies key stakeholders, their roles, and the collaborative mechanisms that can enhance policy effectiveness. The findings suggest that a structured collaboration framework can facilitate better communication, resource sharing, and conflict resolution among stakeholders, ultimately leading to sustainable fishing practices in the region.